Management Strategies for Enhancing Healthcare Workers’ Competence in Erectile Dysfunction Education at a Primary Healthcare Center in Manado City, Indonesia - Grace L.A. Turalaki; Jeffry Sony Junus Lengkong; Joulanda A M Rawis; Rolles N. Palilingan; Ruth Umbase (International Journal of Information Technology and Education, 2025)
Erectile dysfunction (ED) is a prevalent and treatable condition with substantial impacts on men’s quality of life, mental health, and intimate relationships. Despite its clinical importance, ED education at the primary healthcare level remains limited, particularly in sociocultural contexts where sexual health is considered taboo. This study explores healthcare workers’ competence in delivering ED education, identifies supporting and inhibiting factors, and formulates educational management strategies to strengthen ED education at a single primary healthcare center in Manado City, Indonesia. A qualitative case study design was employed. Data were collected from 46 healthcare workers through in-depth interviews, focus group discussions, observations of service delivery, and review of relevant internal documents. Data were analyzed using an interactive approach comprising data reduction, data display, and conclusion drawing (Miles et al., 2014). The findings reveal that healthcare workers’ competence ranges from low to moderate. While biomedical knowledge of ED is generally present, gaps persist in communication skills, empathy, counseling techniques, and culturally sensitive engagement. ED education is often brief, opportunistic, and non-standardized, limiting patient understanding and behavior change. Supporting factors include availability of private counseling space, leadership support, interprofessional collaboration, culturally appropriate educational media, and partner involvement. Inhibiting factors include time constraints, psychological discomfort among healthcare workers, social stigma, limited structured training, and the absence of standardized operating procedures (SOPs) for ED education. The study proposes a competency-based, continuous educational management strategy integrating planning, implementation, and evaluation (POAC), supported by coaching, supervision, and culturally responsive patient education practices. These findings contribute to educational management in healthcare by demonstrating how organizational systems and competence development can strengthen sensitive health education at the primary care level.